THE EMOTION REGULATION HELPS MAIN CHARACTER TO SURVIVE IN MONSTER HUNTER (2020) MOVIE - Iwantara Gata Ryard (CLLiENT (Culture, Literature, Linguistics, and English Teaching), 2021)
Emotion Regulation is a familiar word in today's modern era, even appearing in movies without anyone knowing it. This study discusses the phenomenon of emotion regulation as a method for survival that occurs to the main character in the movie Monster Hunter (2020). This study aims to explain three factors, namely monitoring emotions, evaluating emotions, and modifying emotions in the movie Monster Hunter (2020). Qualitative methods are used in this case to explore the phenomenon of emotion regulation in depth. The research was conducted by applying the theory of emotion regulation by Gross J.J as the basic theory to test the research data. The results of the analysis show that (1) the regulation of emotions revealed to the characters in the Monster Hunter (2020) film has three types, namely monitoring emotions, evaluating emotions, and modifying emotions at each stage. This stage occurs from the events faced by the characters. From the regulation of emotions that occur, this character can take revenge or even the character can think positively and rationally in survival.